(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In India various tremendous environmental problem are rising in construction industry due to leading urbanization. Increasing demands of housing sector which lead to consumes more energy, resources and raw materials which are responsible for the rise in carbon content in air and which are harmful to environment and human health. Nowadays we are facing various environmental impacts due to which we need to build with more sustainable materials which will lead to reduction of impacts on environment. In cities like Pune we are already noticing the change in weather patterns, hotter summers, shorter winters, insufficient monsoons. So taking the preservation of the city‘s ecology and finite energy resources seriously is now more than important. Developers need to find better, more sustainable methods of designing their buildings in order to reduce their negative environmental impact. Therefore it is need of hour to use more sustainable methods and locally available materials which are eco-friendly and a lead for better tomorrow. Considering to all this impacts this paper consist a five green construction materials with their advantages, disadvantages, durability and economical aspects in construction industry which can be an effective alternate material for conventional materials.